Principles of pharmacological therapy of comorbid diseases in patients with orthopedic pathology - Prytula, Nataliya; Fedotova, Inga; Korzh, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Comorbidity is one of the leading problems in clinical practice. Interaction of diseases, involutive processes of natural aging and pathomorphosis of drugs significantly change clinical picture and course of the disease, the nature and severity of complications, limit or complicate the treatment and diagnostic process. Objective. To analyze current information on available recommendations for the treatment of comorbid diseases in patients with orthopedic pathology. Materials. An overview of the recommendations of the European Society of Cardiology, European Society of Hypertension, European Society for Vascular Surgery, Ukrainian Gastroenterological Association and American Diabetes Association for the period 2017–2019 is presented. Results. The first stage in the treatment of arterial hypertension is the lifestyle optimization, and the initial therapy of most patients with hypertension should be a combination of two drugs. Management of patients with lower extremity artery disease is associated with an increased risk of any cardiovascular events. Therefore, preventive measures are of particular importance. Gastropathies induced by non-steroidal anti-inflammatory drugs are widespread in orthopedic practice. In the prevention of their occurrence, a well-chosen gastroprotective therapy is important. Once the diagnosis of diabetes is made, lifestyle modification should be started immediately along with the start of pharmacotherapy. Metformin remains the first-line drug for treatment, drugs of other groups can be prescribed when there are contraindications to metformin. In the treatment of neuropathic pain in diabetes or pre-diabetes, only pharmacological treatment strategies are effective. Conclusions. In most cases, a number of comorbidities with timely diagnosis and compliance with the algorithms of medical care can be corrected and treated. Properly selected conservative therapy can reduce the risk of peri- and postoperative complications.